Organosoluble starch-cellulose binary polymer blend as a quasi-solid electrolyte in a dye-sensitized solar cell - Selvanathan V.; Yahya R.; Ruslan M.H.; Sopian K.; Amin N.; Nour M.; Sindi H.; Rawa M.; Akhtaruzzaman M. (MDPI AG, 2023)
Cellulose; Crystallinity; Electrochemical impedance spectroscopy; Gels; Lithium compounds; Polymer solar cells; Rheology; Solid electrolytes; Starch; Viscoelasticity; Binary polymer blends; Hydroxyethyl cellulose; Organosoluble; Photoconversion efficiency; Rheological characterization; Starch derivatives; Steric hindrances; Viscoelastic properties; Dye-sensitized solar cells; Cellulose; Crystallinity; Gels; Lithium Compounds; Rheology; Starch